The Reliability of Neurological Measurement in the Vastus Medialis: Implications for Research and Practice - Leung, Hans; Latella, Christopher; Lamon, Séverine; Hendy, Ashlee M. (Frontiers in Psychology, 2018)
The integrity of the corticomotor pathway is paramount in the optimal functioning of skeletal muscle. However, variability of neurophysiological assessment via peripheral nerve and transcranial magnetic stimulation can render interpretation difficult. Seldom evidence exists regarding the reliability of such measurements in the leg extensors, which have important locomotive and functional roles. This study aimed to assess the test-retest reliability of peripheral, corticospinal and intracortical responses in the vastus medialis. Transcranial magnetic and direct current electrical nerve stimulation were delivered to sixteen healthy young adults (8M, 8F) on two separate occasions. The Hoffmann reflex, maximal compound wave, motor evoked potential, corticospinal silent period, intracortical facilitation and short-interval intracortical inhibition were recorded from the vastus medialis at rest, and during controlled submaximal voluntary contraction. Relative reliability was quantified using intra-class correlation coefficient (ICC2,1). Absolute reliability was quantified using standard error of measurement (SEm) and minimal detectable change (MDC). Corticospinal silent period, corticospinal silent period/motor evoked potential ratio, active motor evoked potential, maximal Hoffman reflex and passive short-interval intracortical inhibition demonstrated ‘good to excellent’ relative reliability (ICC ≥ 0.643). Intracortical facilitation demonstrated the lowest relative reliability (ICC=0.420-0.908). Corticospinal silent period displayed the lowest absolute reliability (SEm ≤ 18.68%). Good reliability of the maximal compound wave, Hoffman reflex, motor evoked potential and corticospinal silent period allow for reliable neurological evaluation of peripheral and corticospinal pathways in the vastus medialis. Future research should investigate reliability of the intracortical (short-interval intracortical inhibition and intracortical facilitation) measures by using different paired-pulse stimulus parameters. These findings hold important implications for neurophysiological assessment conducted in the leg extensor group.